Herbal medicine for adults with asthma: A systematic review. (2nd July 2016) - Shergis, Johannah L.; Wu, Lei; Zhang, Anthony L.; Guo, Xinfeng; Lu, Chuanjian; Xue, Charlie C.
Abstract: Background : Many people with asthma use herbal medicines to help reduce symptoms and improve asthma control. Objective : To update the systematic review and meta-analysis of randomised controlled trials of herbal medicine for adult asthma. Data Sources : Nine English and Chinese databases were searched (PubMed, Embase, CINAHL, CENTRAL, AMED, CBM, CNKI, CQVIP, Wanfang). Study Selections : Herbal medicines combined with routine pharmacotherapies compared with the same pharmacotherapies alone or placebo. Cochrane Risk of Bias Tool and GRADE Summary of Findings tables were used to evaluate methodological quality. Results : Twenty-nine (29) studies involving 3, 001 participants were included. Herbal interventions used multi-ingredients such as licorice root, crow-dipper, astragali, and angelica. Compared with routine pharmacotherapies alone, herbal medicines as add-on therapy improved lung function (FEV1: MD 7.81%, 95% CI 5.79, 9.83, I 2 = 63%; PEFR: MD 65.14 L/min, 95% CI 58.87, 71.41, I 2 = 21%); asthma control (MD 2.47 points, 95% CI 1.64, 3.29, I 2 = 55%); reduced salbutamol usage (MD −1.14 puffs/day, 95% CI −2.20, −0.09, I 2 = 92%); and reduced acute asthma exacerbations over one year (MD −1.20, 95% CI −1.82, −0.58, one study). Compared with placebo plus pharmacotherapies herbal medicines as add-on therapy improved lung function (FEV1: MD 15.83%, 95% CI 13.54, 18.12 and PEFR: MD 55.20 L/min, 95% CI 33.41, 76.99). Other outcomes were not reported in these placebo studies. Included studies were low to moderate quality. Adverse events were rare. Conclusions : Herbal medicines combined with routine pharmacotherapies improved asthma outcomes greater than pharmacotherapies alone. Included studies did not blind participants therefore more studies that address such weaknesses are warranted.